DNA PANEL DESIGN FOR GENOMIC STUDIES IN RUSSIAN CATTLE BREEDS - N. S. Yudin; L. A. Vasil’eva; V. A. Belyavskaya; R. B. Aitnazarov; P. N. Smirnov; M. Heaton; W. W. Laegreid; G. V. Orlova; A. G. Romashchenko; M. I. Voevoda (Вавиловский журнал генетики и селекции)
A panel of 96 DNA samples that reflects the breadth of genetic diversity in popular Russian cattle breeds has been designed. The panel of cattle DNA contains 11 dairy breeds and 6 beef and beef-dairy breeds. The numbers of animals in each breed group vary from 4 to 8. The main criterion for selection of individual animals within each breed is to maximize the total number of unshared haploid genomes according to pedigree data. The resulting panel is equivalent to USDA MARC Beef Cattle Diversity Panel version 2.1 in the power of SNP identification (number of unshared haploid genomes = 186,1, minimum allele frequency required for its detection with 95 % probability – 1,6 %). Analysis of three SNPs shows an insignificant difference between the allele frequencies in Galloway, Hereford, Grey Ukrainian, and Black Pied herds and those in the panel. Thus, the diversity panel may be useful for identification of genetic markers associated with economically important traits in cattle, evaluation of purebred and crossbred animals, and, probably, for tentative estimation of allele frequencies in commercial populations.